Role of endothelial cells and angiotensin converting enzyme-II in COVID-19 and brain damages post-infection - Mehboob, Riffat; von Kries, Jens Peter; Ehsan, Kashifa; Almansouri, Majid; Bamaga, Ahmed K. (Frontiers in Neurology, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS CoV-2) causes coronavirus disease 2019 (COVID-19), which became a pandemic in late 2019 and early 2020. Apart from many other symptoms of this infection, such as loss of smell and taste, rashes, body aches, fatigue, and psychological and cardiac symptoms, it also causes vasodilation in response to inflammation via nitric oxide release. SARS CoV-2 affects microcirculation, resulting in the swelling and damage of endothelial cells, micro thrombosis, constriction of capillaries, and damage to pericytes that are vital for the integrity of capillaries, angiogenesis, and the healing process. Cytokine storming has been associated with COVID-19 illness. Capillary damage and congestion may cause limited diffusion exchange of oxygen in the lungs and hence hypoxemia and tissue hypoxia occur. This perspective study will explore the involvement of capillary damage and inflammation by their interference with blood and tissue oxygenation as well as brain function in the persistent symptoms and severity of COVID-19. The overall effects of capillary damage due to COVID-19, microvascular damage, and hypoxia in vital organs are also discussed in this perspective. Once initiated, this vicious cycle causes inflammation due to hypoxia, resulting in limited capillary function, which in turn causes inflammation and tissue damage. Low oxygen levels and high cytokines in brain tissue may lead to brain damage. The after-effects may be in the form of psychological symptoms such as mood changes, anxiety, depression, and many others that need to be investigated.